Growth, yield and nutrient uptake of mungbean (Vigna radiata L.) grown in antipolo clay amended with lime, nitrogen and phosphorus fertilizers and microbial inoculants (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
A field trial was conducted to evaluate the effect of liming, application of inorganic nitrogen and phosphorus and inoculation with rhizobia and mycorrhiza on the growth, nitrogen uptake, phosphorus uptake and yield of mungbean at the University of the Philippines Laguna-Quezon Land Grant in Siniloan, Laguna during the wet season of 1997. The interaction between lime, treatment and growth stage significantly influenced dry matter yield. Significant increase in dry matter was obtained with P fertilization which was not observed with mycorrhizal inoculation. Mungbean supplied with P showed varied responses under limed and unlimed conditions. P content of plants grown in unlimed plots was significantly higher than that of plants grown in limed plots. P uptake in P-fertilized mungbean, however, was higher than that in mungbean inoculated with mycorrhiza combined with either inorganic nitrogen or in mungbean inoculated with Bradyrhizobium strain BVr9. Significant interaction between lime, treatment and growth stage was observed in the mungbean shoots' nitrogen content while marked differences in N content of mungbean seed inoculated with mycorrhiza under limed and unlimed conditions were noted. Inoculation with Bradyrhizobium strain BVr9 + P at the rate of 480 kg P 2O5 ha-1 resulted in the highest yield. The second highest yield was obtained in mungbean given 90 kg N ha-1 + 480 kg P2O5 ha-1.